2022
DOI: 10.3390/antiox11091669
|View full text |Cite
|
Sign up to set email alerts
|

Endophytic Fungal Consortia Enhance Basal Drought-Tolerance in Moringa oleifera by Upregulating the Antioxidant Enzyme (APX) through Heat Shock Factors

Abstract: Global climate change has imposed harsh environmental conditions such as drought. Naturally, the most compatible fungal consortia operate synergistically to enhance plant growth and ecophysiological responses against abiotic strains. Yet, little is known about the interactions between phytohormone-producing endophytic fungal symbionts and plant growth under drought stress. The existing research was rationalized to recognize the role of newly isolated drought-resistant, antioxidant-rich endophytic fungal consor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 71 publications
1
23
0
Order By: Relevance
“…Endophytic fungi have also been found to secrete large amounts of secondary metabolites such as terpenoids, alkaloids, phenalenones, cytochalasins, terphenyls, xanthones, diphenyl ether, sterols, squalene, gliotoxins, and their derivatives with varied biological functions (El-Hawary et al, 2020;Rauf et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Endophytic fungi have also been found to secrete large amounts of secondary metabolites such as terpenoids, alkaloids, phenalenones, cytochalasins, terphenyls, xanthones, diphenyl ether, sterols, squalene, gliotoxins, and their derivatives with varied biological functions (El-Hawary et al, 2020;Rauf et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, not all plant species have the capacity to adapt to the changing environment for their survival and growth under stress. Researchers have found that endophytic fungi directly or indirectly induce the resistance of the host plants against various biotic and abiotic stresses ( Rauf et al., 2021 ; Javed et al., 2022 ; Rauf et al., 2022 ) to deal with water stresses by improving water and mineral nutrient uptake, modulating antioxidant capacity to cope with ROS-prone destruction upon stress in plants. Endophytic fungi–assisted drought stress alleviation is a cost-effective and environmentally friendly strategy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations